SISTEM INFORMASI UNTUK MENENTUKAN MENU MAKANAN PENDAMPING ASI (MPASI) BAYI BERDASARKAN ANGKA KECUKUPAN GIZI (AKG) MENGGUNAKAN METODE FORWARD CHAINING - Eka Budhy; Nurul Amri (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
Breastfeeding Food (MPASI) is the stage of baby to start eating after six months consuming only breast milk. Improper feeding of MPASI will be bad in the future, infants will suffering from iron deficiency, the number of nutritional adequacy received is not appropriate with age, and resulted in malnutrition. This happens because of the lack of information that parents get about the intake of MPASI. Therefore, this study proposes the construction of an MPASI menu application taking into account the daily calorie needs of infants using forward chaining method. Stages performed in this research is data collection, analysis of forward chaining method implementation, implementation, and testing using white box. Method of forward chaining in this study using variable weight, age, and gender of the baby. In this research, successfully built the application of the desirable infant menu menu, which is to produce a daily menu of MPASI with the amount of time to eat according to the age of the baby by considering the caloric needs based on the weight and age of the baby. Test results show that the control structure of the application program design is as expected. Keywords: Application Determination of Menu, Calorie Requirement, Forward Chaining Method, MPASI